2010
DOI: 10.1007/s12011-010-8672-7
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Selenium and Vitamin E Inhibits Type I Collagen Formation in Cultured Hepatic Stellate Cells

Abstract: This study investigated the effects of sodium selenite (Se) and of vitamin E (D-α-tochopherol) on the deposition of type I collagen by human LX-2 stellate cells. The cultured cells were treated with or without Se or vitamin E and with or without transforming growth factor β1 (TGFβ1). The combination of Se and vitamin E, but not either alone, protected against hepatic fibrosis by decreasing TGFβ1-mediated collagen secretion and accumulation by the stellate cells. This protective effect is due to a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In line with some studies, the result of the present work indicated that infection of mice with S. mansoni revealed obvious decrease in the non enzymatic antioxidant; GSH, as well as the enzymatic antioxidants including, GR, TrRx, and CAT (Gharib et al, 1999;EL-Sokkary et al, 2002). Treatment with the current micronutrients either alone or in combination, showed an improvement in the antioxidant biomarkers ensuring the antioxidant ability of these agents (Ben Amara et al, 2011;Mezey et al, 2011) The present work showed that the inflammatory reactions and tissue damage induced in livers of S. mansoni infected mice are ensured by marked increase in serum GGT and ALT levels and a decrease in albumin level ( Mohamed et al, 2008;Morais et al, 2010). The increment of such enzymes in serum may be due to the destruction of hepatocytes by the action of toxins of the parasite eggs leading to their release into the circulation (Cheever and Anderson, 1971).…”
Section: Discussionsupporting
confidence: 89%
“…In line with some studies, the result of the present work indicated that infection of mice with S. mansoni revealed obvious decrease in the non enzymatic antioxidant; GSH, as well as the enzymatic antioxidants including, GR, TrRx, and CAT (Gharib et al, 1999;EL-Sokkary et al, 2002). Treatment with the current micronutrients either alone or in combination, showed an improvement in the antioxidant biomarkers ensuring the antioxidant ability of these agents (Ben Amara et al, 2011;Mezey et al, 2011) The present work showed that the inflammatory reactions and tissue damage induced in livers of S. mansoni infected mice are ensured by marked increase in serum GGT and ALT levels and a decrease in albumin level ( Mohamed et al, 2008;Morais et al, 2010). The increment of such enzymes in serum may be due to the destruction of hepatocytes by the action of toxins of the parasite eggs leading to their release into the circulation (Cheever and Anderson, 1971).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with the role of SEPP1 in delivering Se to peripheral tissues for selenoprotein biosynthesis [89, 90], exogenous Se restored expression of GPX3 and TXNRD1 as well as TXNRD1 enzyme activity, depleted TGF β 1-induced ROS downstream of NOX4 induction, and inhibited myofibroblast differentiation of prostatic fibroblasts [26]. Similarly, exogenous Se also inhibited TGF β -mediated myofibroblast transdifferentiation of hepatic stellate cells [91]. Furthermore, we observed that exogenous Se restores morphological and molecular characteristics typical of the fibroblast phenotype to in vitro differentiated prostatic myofibroblasts even in the continued presence of the TGF β differentiation-inducing stimulus [4].…”
Section: Signaling By Nox4-derived Reactive Oxygen Species In the mentioning
confidence: 71%
“…In addition, it has been shown to inhibit the activity of ROS‐generating systems such as iNOS or NADPH oxidase . ROS have been identified as mediators in pulmonary or hepatic fibrosis and antioxidant supplementation has been used to reduce collagen deposition . For instance, Ibuki et al showed how oral supplementation with vitamin E in diabetic, obese mice reduced oxidative stress, decreased the expression of some MMPs and improved skin tensile strength and collagen fibers .…”
Section: Discussionmentioning
confidence: 99%